Technical and Economic Analysis of Conventional and Supercritical Transesterification for Biofuel Production. Issue 10 (17th July 2020) - Nguyen, Dinh Duc; Habibi, Ali; Ghadami, Azam; Pirouzfar, Vahid; Su, Chia-Hung
Abstract: The transesterification process with potassium hydroxide (KOH) catalyst and the methanol supercritical process were evaluated by Aspen HYSYS software. Castor oil and methanol were used as feed and alcohol. In order to accomplish verification, the simulation results were compared to a laboratory research. For economic analysis, these results were transferred to Aspen Economic Analyzer software. Piping and process equipment cost were calculated for the two processes. Additionally, direct and indirect costs of these processes were estimated. Abstract : Two processes of biofuel production from castor oil were investigated. One process was done in the presence of KOH as catalyst and the other one was conducted with supercritical methanol. Both processes were simulated in Aspen HYSYS v10. Final products were biofuel and biodiesel. For validation of the simulation results, the products in the simulation were compared to those of laboratory research.